(8-x)-(9-x)+(8-x)=0

Simple and best practice solution for (8-x)-(9-x)+(8-x)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (8-x)-(9-x)+(8-x)=0 equation:


Simplifying
(8 + -1x) + -1(9 + -1x) + (8 + -1x) = 0

Remove parenthesis around (8 + -1x)
8 + -1x + -1(9 + -1x) + (8 + -1x) = 0
8 + -1x + (9 * -1 + -1x * -1) + (8 + -1x) = 0
8 + -1x + (-9 + 1x) + (8 + -1x) = 0

Remove parenthesis around (8 + -1x)
8 + -1x + -9 + 1x + 8 + -1x = 0

Reorder the terms:
8 + -9 + 8 + -1x + 1x + -1x = 0

Combine like terms: 8 + -9 = -1
-1 + 8 + -1x + 1x + -1x = 0

Combine like terms: -1 + 8 = 7
7 + -1x + 1x + -1x = 0

Combine like terms: -1x + 1x = 0
7 + 0 + -1x = 0
7 + -1x = 0

Solving
7 + -1x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + -1x = 0 + -7

Combine like terms: 7 + -7 = 0
0 + -1x = 0 + -7
-1x = 0 + -7

Combine like terms: 0 + -7 = -7
-1x = -7

Divide each side by '-1'.
x = 7

Simplifying
x = 7

See similar equations:

| X-4y=13fory | | -17=3-x-4x | | 26410=x+0.06 | | 19-13p=-24p-5-(-7p) | | 12x-36y= | | 564t=744t-372 | | 2(8x-4)+4(4x-1)+4(3x)+2(2x)=p | | 2m+8=1076 | | 5-6b=-15+6b-8b | | x^2+6x+81= | | 6x+15=4x+7 | | -5(v+3)+2v+5=5v+8 | | -4(-6a-1)=100 | | X^2-2y^2=0 | | y=-2x^3+5x^2+2x-5 | | 4g+3(-4+4g)=1-g | | 6x+(x+5)=189 | | x^3+2x-2= | | f(x)=-2x^3+5x^2+2x-5 | | 12x^2+16x=3 | | 4(w-5)-2(w+1)=3(1-w) | | X+(2x-75)=90 | | (6-y^5)(6+y^5)= | | -22=3+5u | | 1/2+(2/3/3/4)-(4/5*5/6)= | | -4(4+6b)=80 | | 5z^3-15z^2-1520z=0 | | 2.9=6.9-0.8x | | 3m-3-5=-20 | | 35t=50t-37.5 | | (6xy^2-xy)(6xy^2+xy)= | | 4(y+1)=-6 |

Equations solver categories